2004
DOI: 10.1002/cyto.a.20061
|View full text |Cite
|
Sign up to set email alerts
|

Scanning fluorescent microscopy analysis is applicable for absolute and relative cell frequency determinations

Abstract: Background: Flow cytometry (FCM) and laser scanning cytometry (LSC) are the routine techniques for fluorescent cell analysis. Recently, we developed a scanning fluorescent microscopy (SFM) technique. This study compares SFM to LSC (two slide-based cytometry, SBC, techniques) and FCM, in experimental and clinical settings. Methods: For the relative cell-frequency determinations, HT29 colorectal cancer cells and Ficoll separated blood mononuclear cells (FSBMCs) were serially diluted (from 1:1 to 1:1,000) and mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Although FCM is a proven and reliable highthroughput technology, its major disadvantages for rare event analysis are that high numbers of cells are needed for accurate quantitation, and there is no capacity for morphological analysis (65,66). It has also been suggested that FCM may have limited sensitivity for CTC analysis in human blood samples (67). However, we have found that it has sufficient sensitivity (10 25 ) for use in our animal models when combined with immunomagnetic enrichment, perhaps because of the much smaller overall blood volume of a mouse relative to a human (39).…”
Section: Discussionmentioning
confidence: 99%
“…Although FCM is a proven and reliable highthroughput technology, its major disadvantages for rare event analysis are that high numbers of cells are needed for accurate quantitation, and there is no capacity for morphological analysis (65,66). It has also been suggested that FCM may have limited sensitivity for CTC analysis in human blood samples (67). However, we have found that it has sufficient sensitivity (10 25 ) for use in our animal models when combined with immunomagnetic enrichment, perhaps because of the much smaller overall blood volume of a mouse relative to a human (39).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible to be cytometric (acquiring high number of data on a high number of individual cells) even when images are collected with fluorescent microscope. User friendly software, relocation possibility seems to be an attractive alternative for laser scanning cytometry (LSC) (53)(54)(55).…”
Section: Technology Developments Concerning Slidementioning
confidence: 99%
“…The LSC setup is built around a conventional epifluorescence microscope (11)(12)(13)(14). The scanning fluorescence microscope is a computer-controlled technique with an automated object scanner and data storage (15,16).…”
Section: Slide-based Cytometrymentioning
confidence: 99%